Implementasi Program E-Filing Di Kantor Pelayanan Pajak Batam Dalam Upaya Meningkatkan Kualitas E-Government - Suryani Barimbing Suryani Barimbing (Prodi Ilmu Administrasi Negara, 2023)
The Directorate General of Taxes carried out an initiative to improve e-Government standards, and KPP Pratama Batam implemented SPT reporting via electronic filing. The implementation of the e-filing program is felt to be less effective, as can be seen from the number of taxpayers who prefer to come directly to the tax office rather than contacting them via email or WhatsApp. This shows that the guiding principles of e-Government have not been implemented properly. The aim of this research is to look at the implementation of the E-Filing Program at the Batam Pratama Tax Service Office as part of efforts to improve the quality of e-Government and identify the driving and inhibiting factors. This research uses a qualitative methodology with a descriptive strategy. Based on the research findings, KPP Pratama Batam has successfully implemented the E-Filing program in an effort to improve the quality of e-Government. However, problems such as cash shortages, poor communication, and lack of attitude (or disposition) persist. It is hoped that the challenges of implementing the e-filing program can be resolved soon so that it can run smoothly and efficiently. Keywords: E-Filing, E-Government, Implementation Policy